EVALUATION OF JET-JIT PROTOCOLS AND OBS NETWORK CONFIGURATION FOR NEXT-GENERATION INTERNET - FIRDAUS SYAHID (NIM 23205052), ZAKI
The concept of Next-Generation Internet is developed due to some urgent reasons. These are among other things: the ever increasing demand on network capacity, the bursty characteristic of Internet traffic, and the rapid development of WDM technology. OBS (Optical Burst Switching) is a concept of switching technology proposed for the Next-Generation Internet. In recent years, it has received a lot of attention in optical network research communities, especially because it could minimize electronic bottlenecks at IP layer by creating very high speed all-optical communication channels. In this Thesis, JET and JIT channel reservation schemes are implemented in the simulation environment, and the performances of both schemes are evaluated under various IP/WDM(OBS) network scenarios with bursty traffic and asynchronous IP packets. This Thesis concludes that JET performance is always better than JIT’s, even though the JET’s algorithm is more complicated to be applied. Furthermore, various efficient and feasible OBS network configuration techniques for Next-Generation Internet are introduced.